3D Self-Supported Binary PtCu Aerogel Boosted Methanol Oxidation. Issue 2 (1st February 2022) - Tie, Xiaoguo; Sun, Xiaohan; Li, Qiaoxia; Min, Yulin; Xu, Qunjie
Abstract : Precious metal aerogel has a broad application prospect in the field of fuel cell electrocatalysis because of its unique structure characteristics. In this work, Three-dimensional (3D) self-supporting porous PtCu aerogels have been successfully synthesized via a gelation strategy based on excess NaBH4 . The mass activity of optimized PtCu aerogel in acid methanol solution is 6.56 times higher than that of JM-Pt/C. In addition, the optimized PtCu aerogel showed better stability than JM Pt/C. For the methanol oxidation reaction, the optimized PtCu aerogel still maintains the current density of 930 mA mg −1 Pt after 3600 s Chronoamperometric (CA) test. By X-ray photoelectron spectroscopy (XPS), we demonstrate the electron transfer between Cu and Pt. This would arouse the change of electronic state and atomic spacing on the surface of Pt and endow the PtCu aerogel with both prominent activity and excellent stability due to lattice stress and electron effect. This work provides a strategy for reasonable design high performance fuel cell electrocatalysts.